1996
DOI: 10.1159/000184828
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Beta-Cell Destruction in IDDM The Role of Nicotinamide

Abstract: Autoimmune processes are involved in pancreatic β-cell destruction in type 1 diabetes. Autoantibodies including islet cell antibodies (ICA), glutamic acid decarboxylase antibodies (GADA), and antibodies directed against the 37/ 40 K antigen appear in the circulation years before clinical onset and permit increasingly precise disease prediction. A cellular immune response causes pancreatic infiltration, while macrophages and Th-cells appear to be implicated – via local release of cytokines – in β-cell destructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…Other examples of diseases that stem from cell depletion include Alzheimer's disease (46), Parkinson's disease (47), Huntington's disease (48), blindness caused by loss of retinal photoreceptor cells (49), deafness caused by cochlear hair cell loss (50), and diabetes resulting from ␤ cell depletion (51). In each case, the depletion of highly specialized "terminally differentiated" cells caused by a range of mechanisms and often superimposed on genetic susceptibilities seems to be a common pathway driving progressive organ failure.…”
Section: Discussionmentioning
confidence: 99%
“…Other examples of diseases that stem from cell depletion include Alzheimer's disease (46), Parkinson's disease (47), Huntington's disease (48), blindness caused by loss of retinal photoreceptor cells (49), deafness caused by cochlear hair cell loss (50), and diabetes resulting from ␤ cell depletion (51). In each case, the depletion of highly specialized "terminally differentiated" cells caused by a range of mechanisms and often superimposed on genetic susceptibilities seems to be a common pathway driving progressive organ failure.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that the onset of hyperglycemia is delayed in PARP ϩ͞Ϫ mice suggests that even partial inhibition of PARP is therapeutic. In most patients, when type I diabetes is first diagnosed, the autoimmune process is ongoing, with the pancreas having sustained only a portion of its ultimate damage (41). Thus, treatment with PARP inhibitors at the time of diagnosis may slow disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic patients, niacinamide protects beta cells mainly by blocking PARS activity in response to oxygen free radicals [4]. Gale [11] also showed that nicotinamide protected beta cells against these toxic stimuli of oxygen radicals. The PARS inhibitor, nicotinamide (3 mM), attenuates cell injury and death as well as the increase in PARS activity caused by hydrogen peroxide in human cardiac myoblasts [3].…”
Section: Introductionmentioning
confidence: 99%